Creation of an automated information system using python and the django framework with a telegram bot - Khojiakbar Egamberdiev; Noila Khidirova; Abram Islomov (Big Data and Computing Visions)
This article presents the development of an automated Information System (IS) using Python, the Django framework, and a Telegram bot. The system processes user requests through a chatbot interface, providing data management and retrieval functionalities via a REST API. The integration of Django and Django Rest Framework (DRF) allowed for rapid backend development, while the Telegram bot provided an efficient means of interaction with users. The article describes the system's architecture, development process, and the tools used to implement the solution.